Peningkatan Kualitas Literasi Santri Pondok Pesantren Quran Al-Lathifah Menggunakan Digital Library Maktabah Syamilah - Aceng Badruzzaman; Muhammad Najmuddin Dwi Miharja (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2023)
In the current era of development of science and technology, all information is not only found in print media but also in online media such as e-books, online news, literacy supporting applications such as digital library applications. One of the digital library platforms that might be able to improve the literacy quality of the students is the maktabah syamilah. Among those interested in Islamic studies, the maktabah syamilah is widely known. As the name implies, this maktabah syamilah or comprehensive library is software that includes various books in the field of Islamic studies. Even the books in it can be added or subtracted according to your needs. Maktabah Syamilah's contains almost all the mu'tabarah books in classical Islamic studies and is available free of charge. The method used in this research is descriptive method, with a qualitative approach. With maktabah syamilah, it opens up innovative opportunities for improving the religious learning of santri which is contextual and relevant according to the needs of society. In addition, the maktabah syamilah application can build a good image for non-formal Islamic educational institutions, namely pesantren, in facing modern times and adaptive to change.